Social Stratification in Qatari Society: Family, Marriage, and Khalījī Culture - Hassan, Islam (Hawwa, 2018)
The family in Qatar plays a significant role in shaping its members' lives, passing down the dominant culture with its history, traditions, values, customs, and social order to subsequent generations. Through the institution of marriage, individuals have been choosing their partners based on criteria passed down to them by their families. They have also been preserving and reproducing the culture, traditions, values, and customs invested in them by their own families by reinvesting them into their own children. By relying on a mixed method approach, the author investigates the role of the family and marriage institutions in the sustenance and stimulation of the reproduction of social stratification in Qatari society. This article is the first of its kind to address the phenomenon of reproduction of social stratification in an Arab state of the Persian Gulf.